The hypotensive effect of Yoga's breathing exercises: A systematic review - Brandani, Jeniffer Z. [UNESP]; Mizuno, Julio [UNESP]; Ciolac, Emmanuel G. [UNESP]; Monteiro, Henrique L. [UNESP] (Elsevier, 2017)
The aim of this review was to evaluate the effect of pranayama (Yoga's breathing exercises) on BP and its applicability in the treatment of hypertension. Thirteen trials, assessing acute (eight studies) and chronic (five studies) BP response to pranayama were included. Significant BP reductions after pranayama were found in both acute (2–10 mmHg mean SBP reduction, N = 5 studies; 1 mmHg mean DBP reduction, N = 1 study) and chronic studies (4–21 mmHg mean SBP reduction, N = 3 studies; 4–7 mmHg mean DBP reduction, N = 2 studies). The pranayama's effect on BP were not robust against selection bias due to the low quality of studies. But, the lowering BP effect of pranayama is encouraging. The pranayama with slower rhythms and manipulation of the nostrils, mainly with breaths by the left, present better results when compared with the other types and should be the main pranayama applied when the goal is to reduce blood pressure especially in hypertensive patients.
Keywords: Cardiovascular diseases; Complementary therapies; Hypertension